2009
DOI: 10.1002/adfm.200801049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Property Correlation in Shape‐Controlled ZnO Nanoparticles Prepared by Chemical Vapor Synthesis and their Application in Dye‐Sensitized Solar Cells

Abstract: Here, the large scale synthesis of nanocrystalline ZnO spheres and tetrapods in the size range of 8-40 nm by chemical vapor synthesis using zinc metal as precursor is described. A detailed study of the effect of experimental parameters on the morphology and yield is presented. High-resolution transmission electron microscopy images of the tetrapods show that they are formed by the self assembly of four nanorods in the vapor phase. The tetrapods have optical absorption coefficients that are one order of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 76 publications
1
61
0
Order By: Relevance
“…The tetrapods prepared with the addition of water have longer arms and a lower average diameter (8-20 nm) as compared to tetrapods prepared without water addition [34]. The reaction of Zn metal with water produces hydrogen gas that could favour the production of the suboxide of zinc, which has been reported as the most probable intermediate state in the formation of ZnO tetrapods [35,36].…”
Section: Atmosphere-controlled Oxidationmentioning
confidence: 99%
“…The tetrapods prepared with the addition of water have longer arms and a lower average diameter (8-20 nm) as compared to tetrapods prepared without water addition [34]. The reaction of Zn metal with water produces hydrogen gas that could favour the production of the suboxide of zinc, which has been reported as the most probable intermediate state in the formation of ZnO tetrapods [35,36].…”
Section: Atmosphere-controlled Oxidationmentioning
confidence: 99%
“…The characteristic UV (384 nm, 3.23 eV) and visible (471 nm, 2.63 eV) peaks are observed due to high exciton energy and direct band gap of ZnO. The UV emission in ZnO has been well documented and discussed by many researchers in the literature [23,24]. It is attributed to near band edge transition processes arising from energy loss due to a strong electron-phonon interaction at room temperature [25].…”
Section: Resultsmentioning
confidence: 93%
“…The main function of this layer, aside from the light absorption, lies in the light scattering in the near-infrared region. Its light scattering capability is derived from the sub-micron level pores formed of the nanotetrapods [29]. The inimitable branching structure of our nanotetrapods has imparted this light scattering a certain extent of toughness to endure curvature bending on flexible substrates, a distinct advantage over other kinds of light-scattering materials such as large TiO 2 particle assemblies and SiO 2 sphere photonic-crystals previously applied to DSSCs [62].…”
Section: Zno Nanotetrapod Based Flexible Dsscsmentioning
confidence: 99%
“…This was the first time that DSSC based on pure ZnO nanotetrapod photoanode was demonstrated with a reasonable efficiency; simply by physically contacting the nanotetrapods, the branched nanotetrapods network could effectively transport photoinduced electrons. Later on, Chiu et al [28] and Bacsa et al [29] also reported studies on ZnO nanotetrapods based DSSCs with their photoanodes all calcined at high temperatures.…”
Section: Introductionmentioning
confidence: 96%